1998
DOI: 10.1055/s-1998-1625
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient and Facile Synthesis of Novel 3-Benzoyl-3,4-dihydro-2H-pyrido[1,2-a]pyrimidines

Abstract: The condensation of 1-aryl-2-dimethylaminomethylprop-2-en-1-ones 4 with 2-aminopyridines 5 gives rise to the 3-benzoyl-3,4-dihydro-2H-pyrido[1,2-a]pyrimidines 3. The reaction is initiated by addition of the pyridine amino group to the enone double bond, followed by deamination and ring closure to give the anellated pyrimidine ring system, which is an excellent precursor for the synthesis of pharmacological active compounds.A number of biologically active compounds including antiallergic, 1,2 analgetic, 3,4 ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…The precipitate was filtered, dried and recrystallised from methanol. The yields ranged from 10 to 30% [38,39].…”
Section: General Methods For the Preparation Of Pyrido[12-a] Pyrimidinesmentioning
confidence: 99%
See 2 more Smart Citations
“…The precipitate was filtered, dried and recrystallised from methanol. The yields ranged from 10 to 30% [38,39].…”
Section: General Methods For the Preparation Of Pyrido[12-a] Pyrimidinesmentioning
confidence: 99%
“…After the addition of the nucleophile to the enone structure, the dimethylamino group was eliminated followed by ring closure to form anellated heterocycles [39]. Isolating the resulting products as hydroperchlorates or as hydrochlorides showed that an addition-elimination mechanism had taken place.…”
Section: Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…For the methyl-substituted pyridopyrimidines 5, 6 and 7, the 3 J coupling constants were found to be in the same range. For structures 5, 7 and 8, the 4 J coupling constants were unresolved; for 6, this 4 J coupling constant value was about 1.5-1.8 Hz.…”
Section: H Nmr Datamentioning
confidence: 92%
“…We have shown before that the exchangeable proton is bound to N-1; there is no evidence for tautomeric isomers. [4] The signal of this NH proton is usually rather broad with line widths of several Hz up to 50 Hz (the broadening originating presumably on impurities like traces of excess of acid or water or exchange processes); in some cases, a triplet structure can be anticipated, in those cases the corresponding couplings of this NH proton can be observed in the 4 J(H-7,H-9)] are found. An unresolved 5 J coupling of H-6 with H-9 is observed in the H, H-COSY spectrum of 4, too.…”
Section: H Nmr Datamentioning
confidence: 99%